The use of mindfulness meditation to reduce bargaining anxiety - Wohl, Rachel A. (Henry Stewart Talks, 2014)
Benefits of being a mindful negotiator, Meditation myths, Distinction between mindfulness and mindfulness meditation, Key concepts and meditation techniques, Triangles of breath and awareness, Brief meditation exercises, Setting and following intentions, The STOPSI tool, Using the tool while negotiating